Hubungan Stres Kerja dan Persepsi Beban Kerja dengan Psychological Well-Being pada Anggota Reskrimum Polda Jambi - Muhammad Alfarrel Chandra; Fadzlul Fadzlul; Beny Rahim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Psychological well-being (PWB) represents an essential psychological condition that supports the effectiveness and professionalism of police officers, particularly those working in operational units. Criminal investigation officers routinely encounter complex job demands, strict time limitations, and high responsibility in case handling, which may intensify job stress and perceived workload and ultimately influence PWB. This study aimed to analyze the relationship between job stress and perceived workload with PWB being among officers of the Criminal Investigation Directorate of the Jambi Regional Police. A quantitative correlational approach was applied, involving 130 criminal investigation officers selected through purposive sampling. Data were obtained using online questionnaires consisting of a job stress scale, a perceived workload scale, and a PWB scale. Data analysis was performed using multiple correlation analysis with the assistance of SPSS software. The findings indicated that the majority of respondents were classified within the moderate category for all variables. The results of multiple correlation analysis demonstrated a significant relationship between job stress and perceived workload with PWB, indicated by a correlation coefficient of R = 0.409 with p < 0.001. These results suggest that job stress and perceived workload jointly contribute to variations in PWB of criminal investigation officers.